PENGARUH SUPERVISI AKADEMIK DAN DISIPLIN KERJA TERHADAP KINERJA GURU SMP NEGERI 2 SOSOPAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIATOR - Atri Liani; Noor Hudallah; Arief Yulianto; Suwito Eko Pramono; Sungkowo Edy Mulyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of academic supervision and work discipline on teacher performance through organizational commitment as a mediating variable at SMP Negeri 2 Sosopan. This research employed a quantitative approach with an explanatory design. The population consisted of 54 teachers, and all were selected as respondents using the total sampling technique. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.1. The results indicate that academic supervision and work discipline have a positive and significant effect on organizational commitment. Organizational commitment also has a positive and significant effect on teacher performance. However, academic supervision and work discipline do not significantly affect teacher performance directly. Furthermore, organizational commitment significantly mediates the relationship between academic supervision and work discipline and teacher performance. These findings imply that strengthening teachers' organizational commitment is essential to optimize the impact of academic supervision and work discipline on improving teacher performance.